Analisis penggunaan model think talk and write berbantuan video pada mahasiswa disabilitas - Etriana Meirista; Mitra Rahayu; Karlina Wong Lieung (IKIP PGRI Bojonegoro, 2020)
Abstract: This research is based on findings in the field regarding the existence of children with special needs in the regular classrooms where researchers teach. Students with special needs in the class show symptoms of forfeit and difficult to blend with normal friends in general in class. The situation that occurs is that students with special needs are very enclosed in class, not actively participating in lectures. The independence of students in doing assignments is very low. The existence of an inclusive education curriculum motivates researchers to continue to be able to provide educational services for all students without exception. Students with disabilities referred to in this study were one deaf student and one speech impaired student. This study will describe the independence and motivation of student learning in the classroom with the application of the cooperative model Think Talk and Write (TTW). The research method uses descriptive analysis. Data collection techniques by observation, interview and documentation. The collected data is then analyzed qualitatively including data reduction, data presentation and drawing conclusions. The results showed that the independence and motivation of student learning tended to be good with the active role of the teacher in applying the appropriate learning model. The communication difficulties that existed among students in the class were successfully overcome by the active role of all students in working together in discussion groups. Keywords: hearing impaired, speech impaired, independence Abstrak: Penelitian ini didasari atas temuan di lapangan mengenai keberadaan anak berkebutuhan khusus di kelas reguler tempat peneliti mengajar. Mahasiswa berkebutuhan khusus di kelas tersebut menunjukkan gejala menarik diri dan sulit berbaur dengan teman-teman normal pada umumya di kelas. Keadaan yang terjadi adalah mahasiswa berkebutuhan khusus tersebut sangat tertutup di kelas, tidak berpartisipasi aktif dalam perkuliahan. Kemandirian mahasiswa berkebutuhan khusus dalam mengerjakan tugas sangat rendah. Adanya kurikulum pendidikan inklusi memotivasi peneliti untuk tetap dapat memberikan layanan pendidikan bagi seluruh mahasiswa tanpa terkecuali. Mahasiswa berkebutuhan dimaksud dalam penelitian ini adalah satu orang mahasiswa tuna rungu dan satu orang mahasiswa tuna wicara. Penelitian ini akan mendeskripsikan kemandirian dan motivasi belajar mahasiswa di kelas dengan penerapan model kooperatif tipe Think Talk and Write (TTW). Metode penelitian menggunakan analisis deskriptif. Teknik pengumpulan data dengan observasi, wawancara dan dokumentasi. Data yang terkumpul kemudian dianalisis secara kualitatif meliputi reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa kemandirian dan motivasi belajar mahasiswa cenderung baik dengan adanya peran aktif guru dalam mengaplikasikan model pembelajaran yang sesuai. Kesulitan komunikasi yang ada diantara mahasiswa di kelas berhasil diatasi dengan peran aktif seluruh mahasiswa dalam bekerja bersama dalam kelompok diskusi. Kata kunci: tunawicara, tunarungu, motivasi, kemandirian